Relevansi Manajemen Madrasatul Ula dalam Penguatan Pendidikan Karakter: Analisis Historis dan Komparasi Praktik Modern - Sabri, Muhammad (Jurnal Manajemen dan Budaya, 2025)
The Indonesian education system needs a more holistic foundation and model of character education, centered on the instillation of values. This study aims to analyze in depth the relevance of Madrasatul Ula management in strengthening character education with three key questions: 1) How can the historical foundation of character education in the early Islamic period become a relevant prototype for modern education?, 2) What are the fundamental similarities and differences between this historical educational model and contemporary educational practices?, 3) How can modern challenges be addressed by reintegrating the principles of Madrasatul Ula? To answer these questions, the researcher collected data from various sources consisting of books, journal articles, dissertations, and scientific works related to Islamic education management, the history of Islamic education, and character education theory. The analysis process includes data reduction, grouping findings, and then interpreting the findings. To maintain the validity of the data, this study applies source triangulation. The results of this study found that strengthening character education in Indonesia can be successful if all stakeholders return to making Madrasatul Ula as a foundation, with management and pedagogy that exemplify the leadership of the Prophet Muhammad.